Decarbonizing strategies of the retail sector following the Paris Agreement - Ferreira, Ana (2019)
The retail industry is one of the top 10 most carbon-intensive sectors. This paper is original in addressing what has changed in corporate retail with the Paris Agreement, accessing trends to decarbonize the sector. A qualitative comparison was performed regarding the policy, strategy and energy-related building solutions of the top 27 global retailers, ranked according to their revenue, regarding the reporting periods of 2014-2015 and 2016-2017. For each retailer, data were searched on retailers? sustainability reports was organized in different tables according to the variables policy, strategy and energy-related building practice. A comparison analysis was carried out, in order to identify differentiating decarbonizing measures. Corporate governance is increasingly relevant to manage climate change issues. Strategies to decarbonize the retail sector include establishing ambitious energy goals, invest in sustainability of supply chain with more efficient logistics and in greener retail operations, with buildings designed and managed under a life-cycle perspective (energy-efficiency, renewable energy and natural refrigerants). Retailers are progressively aligning their energy targets to those of the Paris Agreement and converging in business principles and reporting standards. With forthcoming regulation on GHG emissions, retailers could benefit from a business case on low-carbon opportunities and financial incentives to accelerate low-carbon transition investments.